含食物类汉语与印尼语成语对比研究A Comparative Study of Chinese and Indonesian Idioms Containing Food Elements - Lestari Puspita Ningsih; Jin Xiao Yan (Universitas Tanjungpura, 2022)
中国与印尼两国的语言具有很丰富的成语。目前还没有学者对汉语与印尼语食物类成语进行过对比研究，所以该文章不仅能为印尼学生更容易理解和掌握含食物类汉语成语，也为中国学生学习印尼语成语提供参考。该文章的研究方法主要把《汉语成语大词典》与《7700 Peribahasa Indonesia》两本成语词典进行对比分析。通过对搜集到的文献进行统计数据而分析，进行归纳、描述和解释研究结果。该文章的研究结果不但找出含“食物类”的汉语与印尼语成语，而且也发现两种语言的成语是被影响当地的自然条件和风俗习惯。Chinese and Indonesian languages are rich in idioms. Until the present, there have been no scholars who have conducted comparative research on Chinese and Indonesian idioms containing food elements. This article not only makes it easier for Indonesian students to understand and master Chinese idioms containing food elements but also provides a reference for Chinese students to learn Indonesian idioms. The research method of this article mainly compares and analyzes two idiom dictionaries,